Structure–reactivity relationships for aromatic molecules: electrostatic potentials at nuclei and electrophile affinity indices. (8th August 2012) - Galabov, Boris; Ilieva, Sonia; Koleva, Gergana; Allen, Wesley D.; Schaefer III, Henry F.; von R. Schleyer, Paul
Abstract: Recent advances have been achieved in the quantitative description of the reactivity of aromatic compounds in terms of simple parameters derived from theoretical computations. The first part of this review surveys the use of electrostatic potentials at nuclei (EPN) in characterizing the reactivity of substituted aromatic compounds when the reaction center is situated outside the aromatic ring. The application of EPN for several typical reactions of substituted aromatic systems is described in detail. The performance of alternative reactivity descriptors, such as theoretical atomic charges, the Parr electrophilicity index, and the experimental Hammett constants, is considered as well. The second part of this review discusses the recently proposed electrophile affinity construct for quantifying reactivity and regiospecificity for the most typical reaction of arenes: electrophilic aromatic substitution. The characterization of reactivity of aromatic molecules in terms of proton affinities and arene nucleophilicity indices is surveyed briefly. This article is categorized under: Structure and Mechanism > Molecular Structures Abstract :